Modelling The Relationship of Perceived Quality, Destination Image, and Tourist Satisfaction at The Destination Level - Ky Vien, Nguyen (International Journal for Applied Information Management, 2021)
Today, the tourism sector in Vietnam has increasingly been a key element in job creation, economic development, and poverty alleviation. With its well-preserved cultural and natural diversity, Vietnam has been becoming a spotlight in the global tourism map. However, many tourist destinations in Vietnam are now struggling with ways to improve tourists’ satisfaction level and increase the return rate of tourists. Therefore, the tourism industry and government have to acknowledge how the tourists experienced and perceived the quality of a destination and the possibility of their return. The purpose of this study is twofold. Firstly, the study evaluates how tourists perceive the service quality of a tourist destination. Secondly, the study attempts to build a conceptual model linking tourists’ perceived quality, destination overall image and tourist satisfaction at the destination level. The study suggests more directions for future research: continuing to test the empirical validation and reliability of the conceptual model for a certain case study in Vietnam, and continuing to examine the moderating effects of the different demographic characteristics of the tourists (i.e. gender, age groups) on the relationships between tourists’ perceived quality, destination overall image and tourist satisfaction at the destination level.